Studying activities that take place in speech interactions: a theoretical and methodological framework. Issue 5 (27th May 2016) - Saint-Dizier de Almeida, Valérie; Colletta, Jean-Marc; Auriac-Slusarczyk, Emmanuelle; Specogna, Antonietta; Simon, Jean-Pascal; Fiema, Gabriela; Luxembourger, Christophe
Abstract: The paper proposes a theoretical and methodological framework based on a pluralistic, concerted approach to the study of activities that take place in and through speech interactions. The framework has a general scope, applying to any collective activity taking form through language interactions. It contributes to a fuller understanding of the dynamics of activity and the emergence of the phenomena observed. The framework fits a constructivist and interactionist paradigm. It allows an approach to different dimensions of the activity: communicational, functional, discursive and interlocutory. The theories, models, concepts and methods chosen to address each of the dimensions are presented. From the study of a collaborative philosophical inquiry produced in the first year of a French primary school, we illustrate the use of the framework and show how it can be enriched according to the nature of the activity studied and researchers' aims.